EXPLORATION OF THE CONTRALATERAL GROIN IN PAEDIATRIC INGUINAL HERNIA OR HYDROCELE BASED ON ULTRASOUND FINDINGS - IS IT JUSTIFIED? - Zaidi, Syed Hashim; Rahman, Javed Ur; Siddiqui, Tariq Saeed; Rehman, Habib Ur; Ahmed, Naveed; Fraz, Muhammad Omar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Routine exploration of contralateral side in cases of unilateral inguinal hernia or hydrocele is a highly debatable topic because of various reasons. The purpose of this study was to analyse whether the contralateral groin exploration in unilateral inguinal hernia/ hydrocele is justified or not, based on ultrasonographic measurements of the inguinal ring diameter. Methods: This cross-sectional study was conducted at two naval hospitals, PNS Rahat and PNS Shifa in Karachi, Pakistan, from June 2007 to Aug 2012. Children presenting with unilateral inguinal hernia or hydrocele were included in the study. Ultrasound examination of the contralateral, apparently normal, groin was carried out using a high-resolution 7.5-11 MHz linear array with the patients in supine position. Surgical exploration of the contralateral groin was carried out in those children in whom the diameter of the inguinal canal at the internal ring was 4.5 mm or greater. All those children in whom the contralateral exploration was not done were followed up to 2 years. Results: A total of 287 patients completed the study, including 264 (92%) boys and 23 (8%) girls. In 242 (84%) cases, the mean diameter of internal ring on contralateral (clinically uninvolved) side was 3.5± 0.4 mm, considered negative. Out of these 13 (5.4%) cases, however, proved to be false negative after a follow up of two year. There were 45 (16%) cases that underwent contralateral exploration on basis on positive ultrasound findings; 25 (55.6%) were hernias and 14 (31.1%) were hydroceles. In the remaining 6 (13.3%) cases surgical exploration failed to demonstrate hernia or PPV. Conclusion: Contralateral exploration in children with unilateral inguinal hernia or hydrocele, based on ultrasonographic findings, is not only cost effective but can also prevent unnecessary routine contralateral explorations and complications related to inguinal hernias. Keywords: Inguinal hernia; Patent process vaginalis; Hydrocele; Contralateral exploration; Ultrasonography; Internal ring diameter